Dinamika Struktur Komunitas Mikroalga Kodominan Waduk Sutami Malang Akibat Penambahan Variasi Konsentrasi Deterjen secara Ex-Situ - Titik Wijayanti (IKIP Budi Utomo Malang, 2019)
The study aims to determine the response of microalgae community structure codominant and abiotic factors change Sutami Malang waters due to the addition of the detergent concentration variation in ex-situ. The experiment was conducted in September 2007 to March 2008. The addition of the detergent concentration consists of four levels, namely D0 (0 ppm), D1 (0.1 ppm), D2 (2 ppm) and D3 (4 ppm) of detergent to the water reservoir. Variable dynamics of microalgae abundance and abiotic factors waters observed simultaneously and periodically every five days for 40 days. The results showed that increasing the concentration of detergent changing dynamics of microalgae community structure codominant. Detergents suppress the growth Ceratium at a concentration ≥ 0.1 ppm. Instead detergent Synedra population increases until day 30 and stimulate the growth of Microcystis. During the 40 days of observation, abiotic factors change due to the addition of detergent concentration, especially the increase in conductivity, Total Organic Matter, phosphate, nitrate and surfactant. In contrast to lower CO2-free detergents and Dissolved Oxygen. Changes in abiotic factors significantly affect the growth of microalgae codominant.